A Model of Seismic Velocity Structure Derived from Local Tomographic Inversion Beneath the Jailolo Mountain Complex, North Maluku - Wandono, Wandono; Nanda, Bayu Merdeka Tri Fristiyan; Heryandoko, Nova; Karyono, Karyono (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
In late 2015, the Mount Jailolo complex was shaken by a prolonged earthquake swarm. Mount Jailolo is an ancient volcano that has shown no activity since 1600. The occurrence of an earthquake swarm in the region has sparked speculation about a resurgence of volcanic activity at this ancient volcano. To study the swarm phenomenon in Jailolo, a local scale high-resolution seismic tomography study with a nonlinear approach was conducted beneath the Mount Jailolo complex —a first of its kind. The primary objective of this study is to image the P- and S-wave velocity structures in the upper crust down to a depth of 15 km in 3D for the Mount Jailolo complex (0.8°–1.3° N; 127.2°–127.9° E). Using data from 524 microearthquakes that occurred beneath the Mount Jailolo complex, collected by the GFZ-Potsdam and BMKG collaborative seismic network over a 12-month period, a negative S-wave velocity anomaly was detected beneath Mount Jailolo at depths below 5 km, which is believed to correspond to a magma chamber. The upper crust at depths of less than 5 km is dominated by positive P- and S-wave velocity anomalies, except in the Idamdehe Caldera Complex, west of the Mount Jailolo complex, which is characterized by negative velocity anomalies. The positive velocity anomalies are believed to represent igneous rocks resulting from past volcanic activity at Mount Jailolo.